Toxicological studies of Darvyadi Kvatha Curna using albino rats (Stamford Journal of Pharmaceutical Sciences, 2012)
Darvyadi Kvatha Curna (DVY), is an Ayurvedic preparation which is used in leucorrhoea in the rural population as a traditional medicine. This Ayurvedic preparation was administered chronically to the male and female rats to explore the toxicological characteristics of this preparation. After the administration of DVY preparation for a period of 45 days, the following biochemical parameters (protein, albumin.triglyceride, cholesterol, LDL, VLDL, HDL, creatinine, uric acid, urea, and bilirubin) in the plasma of both the male and female rats were determined. In the study the total protein content in the plasma was increased (2.75%) in the DVY treated male rats. The result showed no significant difference between the control and the DVY treated groups; but the p value, though was not significant yet it was noticeable (p=0.073). Interestingly, the albumin content was significantly increased (17.21%) in DVY treated male rats. In the female rats group the total protein and the albumin content in the plasma were also increased in comparison to their control groups. A statistically significant (13.46%) increase was noted only in the case of albumin. In the male rats there was a significant decrease in the Triglycerides content in the plasma. After chronic administration of the traditional medicine the triglyceride level was 31.15% decreased in male rats group. Also insignificant decrease was noted in the total Cholesterol and HDL content in the plasma with 4.12% and 1.07% decrease respectively. Besides insignificant increase was noted in the VLDL content in the plasma with 18.16% increase. But only in the case of the content of the LDL in plasma a significant decrease (12.72 % decr.) was noted. In the female rats there was a significant decrease in the Triglycerides content in the plasma. Here the test medicine also decreased the triglyceride level by 9.47% in female rats group. Also an insignificant decrease in the total Cholesterol, VLDL, LDL and HDL content in the plasma was noted with 4.12 %, 6.94 %, 2.46 % and 0.78 % decrease respectively. In the male rats there was a significant decrease (51.37 %) in the Bilirubin content in the plasma. In the female rats there was a significant increase (33.38 %) in the Bilirubin content in the plasma. There was an increase in the plasma creatinine (2.28 %) in the DVY treated male rats, though this increase was not significant, yet noticeable (p=0.072). On the contrary, a significant decrease in the urea (11.90%) content in plasma was noted. In female rats, there was a significant decrease in both the Creatinine (36.60 %) and Urea (7.72%) content in the plasma. It was observed that about 11.71% decrease in plasma uric acid content of DVY treated male rats in comparison to their control male rats which is statistically significant. It was observed that the female rats showed significant increase in the concentration of uric acid (11.68%) level in comparison to their control female rats.DOI: http://dx.doi.org/10.3329/sjps.v4i2.10438  S. J. Pharm. Sci. 4(2) 2011: 29-34